Development and Validation of an Instrument for Assessing Distance Education Learning Environments in Higher Education: The Distance Education Learning Environments Survey (DELES) - Walker, S.; Fraser, Barry (Kluwer Academic Publishers, 2005)
The purpose of this study was to develop and validate a new learning environments instrument designed to aid investigators and practitioners in measuring and researching the psychosocial learning environment in post-secondary distance education. Using a three-stage approach, the Distance Education Learning Environments Survey (DELES) was developed, field-tested with 680 distance education students, and then validated. The DELES has 34 items allocated to six scales: (1) Instructor Support; (2) Student Interaction and Collaboration; (3) Personal Relevance; (4) Authentic Learning; (5) Active Learning; and (6) Student Autonomy. An additional scale of Enjoyment was included in this study to explore associations between the psychosocial learning environment and student affective traits. Each learning environment item had a factor loading of at least 0.50 with its own scale, and less than 0.50 with all other scales. The alpha reliability coefficient for each scale ranged from 0.75 to 0.94. Simple correlations between Enjoyment and the DELES scales ranged from 0.12 to 0.31, with the scale of Personal Relevance having the strongest correlation with Enjoyment when all other scales were mutually controlled. The DELES, an online instrument that can be utilized by students at any location, eliminates data transfer errors and does not allow for non-responses, adding to the overall validity of the instrument. The development of DELES relied extensively on literature pertaining to high-quality distance education and expert content validation techniques. It treats distance learning as having a distinct social-psychological climate unlike those found in other post-secondary classroom environments.